From theme to quality: Investigating thematic progression in IELTS writing - Farida, Alief Noor (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Coherence is one of the indicators of good writing, especially in high-stakes proficiency tests, like IELTS. Very few studies have been conducted on the thematic progression of IELTS writing, especially to compare the quality of the essays across different bands. This study aims to explore the thematic progressions employed in IELTS Writing band 2 essays, from bands 4 – 9. By doing quantitative and qualitative text analysis on 30 argumentative essays, which responded to the same prompt, the thematic progressions and thematic breaks were analyzed. The study revealed that all types of thematic progressions are employed by the essays from different bands, with different portions, while breaks mostly occur at low-band essays. This confirms the importance of incorporating thematic progressions in writing instructions, so student learn that they need to plan their writing structure to make is more persuasive.